2004
DOI: 10.1562/2004-05-26-ra-179
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT DEFENSES AND DNA DAMAGE INDUCED BY UVA AND UVB RADIATION IN THE CRAB Chasmagnathus granulata (DECAPODA, BRACHYURA)

Abstract: The photoprotector role of pigment dispersion in the melanophores of the crab, Chasmagnathus granulata, against DNA and oxidative damages caused by UV-A and UV-B was investigated. Intact and eyestalkless crabs were used. In eyestalkless crabs, the dorsal epidermis of the cephalothorax (dispersed melanophores) and the epidermis of pereiopods (aggregated melanophores) were analyzed. Intact crabs showed only dispersed melanophores in the two epidermis. Antioxidant enzymes activity and lipoperoxidation content wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Their embryos, spermatozoa, haemocytes, hepatopancreas and gill cells were assayed for the possible genotoxic effects of heavy metals, coal combustion residues, phototoxicants, PAHs, UV radiation and other environmental stressors. Various species -Acartia tonsa [296], Corophium volutator [299], Chasmagnathus granulata [300], Callinectus sapidus [301], Carcinus maenas [87], Charybdis japonica [302] and Eriocheir sinensis [303] have been studied for DNA-damaging effects of UV irradiation and contaminants such as heavy metals, herbicides and oil.…”
Section: Several Species Inhabiting Mostly Inland Saltwater Lakes Sumentioning
confidence: 99%
“…Their embryos, spermatozoa, haemocytes, hepatopancreas and gill cells were assayed for the possible genotoxic effects of heavy metals, coal combustion residues, phototoxicants, PAHs, UV radiation and other environmental stressors. Various species -Acartia tonsa [296], Corophium volutator [299], Chasmagnathus granulata [300], Callinectus sapidus [301], Carcinus maenas [87], Charybdis japonica [302] and Eriocheir sinensis [303] have been studied for DNA-damaging effects of UV irradiation and contaminants such as heavy metals, herbicides and oil.…”
Section: Several Species Inhabiting Mostly Inland Saltwater Lakes Sumentioning
confidence: 99%
“…Previous studies have reported enhanced survival and reproduction of invertebrates with an increase in vitamins and/or antioxidants (e.g. B 12 is required in Daphnia pulex for the development of viable offspring [ 21 ]; vitamin D is required to maintain fecundity in Moina [ 22 ]); antioxidants are required by Chasmagnathus granulata following UV-induced DNA damage [ 23 ]). It is theorized that vitamins taken up from the environment, either from natural production or terrestrial runoff, may play an important role in the overall fitness of an organism.…”
Section: Introductionmentioning
confidence: 99%